2010
DOI: 10.1177/1087057110363823
|View full text |Cite
|
Sign up to set email alerts
|

AlphaScreen®-Based Characterization of the Bifunctional Kinase/RNase IRE1α: A Novel and Atypical Drug Target

Abstract: IntroductIon Large-scale technologies used within the life science industry for drug discovery have recently proven useful in academic research laboratories, facilitating chemical genomics and the investigation of specific biological functions. these technologies, including homogeneous luminescence (e.g., alphascreen ® and aequorin), fluorescence intensity (fi) or polarization (fP), time-resolved fluorescence (trf), laser scanning cytometry, or microscopy-based approaches, have become enabling tools to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…In one very important study, Lin et al (2007), showed that prolonging IRE1 signalling improved cellular viability and delayed the onset of apoptosis, suggesting that developing drug targets that stimulate IRE1 signalling could be a viable strategy for preventing cell loss. The importance of IRE1 as a target was also recognised by Bouchecareilh et al, who developed a high-throughput screening assay to monitor the dimerization/oligomerization and phosphorylation properties of the cytosolic domain of IRE1 [129]. They show in vitro that dimerization/ oligomerization of the cytosolic domain of IRE1 correlates with the autophosphorylation ability of this domain and its endoribonuclease activity toward XBP1 mRNA.…”
Section: Potential Targets For Future Drug De-velopment and Clinical mentioning
confidence: 93%
“…In one very important study, Lin et al (2007), showed that prolonging IRE1 signalling improved cellular viability and delayed the onset of apoptosis, suggesting that developing drug targets that stimulate IRE1 signalling could be a viable strategy for preventing cell loss. The importance of IRE1 as a target was also recognised by Bouchecareilh et al, who developed a high-throughput screening assay to monitor the dimerization/oligomerization and phosphorylation properties of the cytosolic domain of IRE1 [129]. They show in vitro that dimerization/ oligomerization of the cytosolic domain of IRE1 correlates with the autophosphorylation ability of this domain and its endoribonuclease activity toward XBP1 mRNA.…”
Section: Potential Targets For Future Drug De-velopment and Clinical mentioning
confidence: 93%
“…Bacteria were then collected by centrifugation, lysed, and recombinant proteins purified as recommended by the manufacturer (Gibco BRL). The resulting purified proteins were concentrated and dialyzed using Amicon ultra centrifugal filters (cutoff = 20,000 Da; Millipore Corp.), followed by functional testing as previously described (12, 13). …”
Section: Methodsmentioning
confidence: 99%
“…Total RNA (10 μg) from U87 or HepG2 was incubated with the cytoplasmic domain of human GST-IRE1α (5 μg) at 37°C for the indicated amounts of time in a buffer containing 250 mmol/L Tris pH 7.5, 600 mmol/L NaCl, 5 mmol/L MgCl2, 5 mmol/L MnCl2, 25 mmol/L β-mercaptoethanol, supplemented with or without 10 mmol/L ATP as previously described (12). As control, we used heat-denatured GST-IRE1α.…”
Section: Methodsmentioning
confidence: 99%
“…Its role in cancer progression was also documented along this axis, showing an activation of the pathway inducing proliferation in colorectal carcinoma cells [26]. It was identified as a druggable target and potential therapeutic option in multiple myeloma [27, 28] and seems to be amplified in 8% of invasive breast cancers [18, 19]. Nevertheless most of these studies focused on the role of Xbp1 alternative splicing.…”
Section: Discussionmentioning
confidence: 99%